Annual greenhouse gas fluxes from a thin-layer rooftop lawn - Masuda, Shohei; Mito, Takuya; Morii, Misago; Kuronuma, Takanori; Watanabe, Hitoshi (Frontiers in Environmental Engineering, 2025)
Green roofs are a key solution for increasing green spaces in urban areas covered with impervious surfaces. In recent years, there has been growing interest in the ability of green spaces to reduce greenhouse gas (GHG) emissions and enhance carbon sequestration. To investigate whether green roofs contribute to GHG reduction, it is essential to quantify both carbon sequestration and GHG fluxes. However, few studies have investigated GHG fluxes from green roofs over the long term. To address this gap, this study measured and quantified the annual GHG (carbon dioxide (CO2), methane (CH4), nitrous oxide (N2O)) fluxes from a thin-layer rooftop lawn using clear acrylic automatic open/close chambers. In addition, we calculated CO2 sequestration based on the difference between total carbon contents in rooftop lawns (soil and turf) at the beginning and end of the experiment. The annual CO2, CH4, and N2O fluxes were calculated to be −1762 g-CO2• m-2• year-1, 92.33 mg-CH4• m-2• year-1, and 0.53 mg-N2O•m-2• year-1 respectively, and CO2 sequestration by plants and soil was estimated to be −2,626 g-CO2•m-2•year-1 during the first year after construction. The CH4 and N2O fluxes from the rooftop lawn were significantly lower than those reported in other studies conducted on ground-level lawns. Based on these results, annual GHG emission (total of CO2, CH4, and N2O) from the rooftop lawn were calculated to be −1759 to −2,623 g-CO2e (CO2 equivalents). m-2• year-1, indicating that the rooftop lawn acts as GHG sink.